2020
DOI: 10.26911/thejmch.2020.05.05.12.
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Amniotic Meconium and Low Birth Weight as Predictors of Asphyxia in Newborns

Alfiati Nanda Widiyaningrum,
Eti Poncorini Pamungkasari,
Bhisma Murti

Abstract: Background: Preterm birth, intrapartumrelated complications (birth asphyxia or difficulty breathing at birth), infections and birth defects accounted for the majority of neonatal deaths in 2017. Low birth weight and amniotic fluid with meconium are factors associated with perinatal asphyxia. The aim of this study was to conduct a meta-analysis to estimate the influence of meconium in the amniotic fluid and low birth weight on the risk of asphyxia in newborns based on the results of previous similar studies. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…The results of meta-analysis of 7 studies evidenced that birth weight < 2500 gram were 4.82 times (AOR:4.82,95%CI:3.72-5.91) more likely to have low 5th minute Apgar score as compared to newborn with birthweight > 2500 gram among newborns in Ethiopia. This is in lined with meta-analysis reported that low birth weight had low Apgar score (32).This might be due to the fact that low birth weight occurs as a result of maternal complications before conception or antepartum period.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of meta-analysis of 7 studies evidenced that birth weight < 2500 gram were 4.82 times (AOR:4.82,95%CI:3.72-5.91) more likely to have low 5th minute Apgar score as compared to newborn with birthweight > 2500 gram among newborns in Ethiopia. This is in lined with meta-analysis reported that low birth weight had low Apgar score (32).This might be due to the fact that low birth weight occurs as a result of maternal complications before conception or antepartum period.…”
Section: Discussionsupporting
confidence: 85%
“…This review showed that meconium-stained amniotic uid were signi cantly associated with low 5-minute Apgar score. These ndings were similar to systematic review done on effects of meconium-stained amniotic uid and low birth weight on birth asphyxia (32,33).The possible reason might meconium-Page 8/13 stained amniotic uid had major impact on mode of delivery and newborn outcome.…”
Section: Discussionsupporting
confidence: 84%